2013
DOI: 10.1039/c3ob27239g
|View full text |Cite
|
Sign up to set email alerts
|

Phosphomolybdic and phosphotungstic acids as efficient catalysts for the synthesis of bridged 1,2,4,5-tetraoxanes from β-diketones and hydrogen peroxide

Abstract: Phosphomolybdic acid (PMA) and phosphotungstic acid (PTA) efficiently catalyze the addition of H2O2 to β-diketones to form bridged 1,2,4,5-tetraoxanes. These reactions are not accompanied by the formation of monocyclic peroxides containing hydroxy and hydroperoxide groups or polymeric peroxides. The use of these catalysts made it possible to obtain bridged tetraoxanes from easily oxidizable benzoylacetone derivatives and α-unsubstituted β-diketones. The syntheses are scaled up to ten grams. The resulting perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 72 publications
3
21
0
Order By: Relevance
“…13 C NMR (75.48 MHz, CDCl 3 ): δ =10.0, 14.2, 22.7, 24.0, 27.8, 29.6, 31.7, 59.3, 111.0 ppm. The physical and spectral data were consistent with those previously reported …”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…13 C NMR (75.48 MHz, CDCl 3 ): δ =10.0, 14.2, 22.7, 24.0, 27.8, 29.6, 31.7, 59.3, 111.0 ppm. The physical and spectral data were consistent with those previously reported …”
Section: Methodssupporting
confidence: 91%
“…For this reason, the selective synthesis of peroxides on the basis of diketones is a very difficult task. We have found that the selective synthesis of peroxides can be carried out by peroxidation of β‐diketones catalyzed by strong acids (e.g., H 2 SO 4 , HClO 4 , HBF 4 , and BF 3 ⋅ Et 2 O) and heteropolyacids (e.g., phosphomolybdic, phosphotungstic) . Peroxidation of β,δ′‐triketones employing heteropolyacids as a catalyst leads to the formation of bridged keto‐tetraoxanes, bridged keto‐ozonides, and tricyclic monoperoxides .…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…The use of these catalysts made it possible to obtain bridged tetraoxanes from easily oxidizable benzoylacetone derivatives and α-unsubstituted β-diketones [429]. …”
Section: Reviewmentioning
confidence: 99%